Legal Construction of the Use of Big Data to Support Sustainable Innovation in the Digital Era - Sua Fauzan; Tri Susilowati; Lamijan, Lamijan (LPPM Universitas Ekasakti Padang, 2024)
The legal framework governing the use of big data has become a crucial issue in this digital era. One notable advantage of Big Data and Computational Technology is the enhanced ease of storing and retrieving records. With platforms such as social media, individuals are storing a greater volume of data than ever before. The likelihood of having physical copies of old photographs has diminished or they have been discarded, yet numerous individuals have already shared them on social media platforms. This research employs qualitative methods with data collection techniques using library research. In Indonesia, there are currently no specific regulations governing the use of Big Data. However, the Principles of the Indonesian Digital Economy have recognized the need for data protection as a crucial asset. It indicates that the legal construction regarding Big Data usage is an urgent issue. In the case of Big Data, platforms or infrastructures that store, manage, and provide access to large data can be considered Essential Facilities. The main challenge in regulating Big Data lies in the technical complexity and cross-border nature of the data. Limitations of national jurisdiction and the lack of a comprehensive international framework make it difficult to regulate data ownership and access effectively.